PENGETAHUAN GENERASI MUDA BANJAR ATAS LEKSIKAL FLORA DAN FAUNA KALIMANTAN SEBAGAI WACANA PELESTARIAN LINGKUNGAN - Aisyah, Siti Sophia (Hasta Wiyata, 2023)
This study aims to reveal Malang Banjareseâ€™s young generation foreigner knowledge on Borneo flora fauna lexical and itâ€™s used in terms of phonology and grammatical. An instrument in this research is a questionnaire that contains flora fauna lexical from Banjarese literature. The literature is folklore, folksong, rhyme, proverb, and poetry. There are 60 subjects taken based on specific criteria. Interviews were conducted to 10 persons. In addition, focus group discussion is held to reveal some data that may not be revealed through the questionnaire. The research results show that Banjareseâ€™s young generation knowledge on Borneo flora and fauna lexical is dominant in â€œvery lowâ€ prologue. On the other side, thereâ€™s phonological process found in bidawang lexical as sound substitution and neutralization so itâ€™s turned into pidawang, didawang, and di gawang. Di gawang pronunciation changes the meaning from â€˜animalâ€™ to â€˜wicketâ€™. This is caused by deforestation that makes the younger generation of Banjareseâ€™s doesnâ€™t know that bidawang is an animal because this animal canâ€™t be found in the wild. On the other hand, thereâ€™s a gap in this study (research gap) as this research does not provide all the young generation of Banjareseâ€™s in early adolescence or young generations of Banjareseâ€™s that werenâ€™t going overseas or have a different background. Hence, this study can be developed by widening the scope of the research subject (in this case the young generation of Banjareseâ€™s).